Оптимізація розподілу навантаження між розосередженими джерелами енергії в локальній електричній системі - Лежнюк, П.Д.; Нікіторович, О.В.; Нетребський, В.В. (Технічна електродинаміка, 2012)
The system of optimal management is examined by the dispersed sources of electric power in the in-plant electric system. The system of automatic control is built on the basis of principle of the least action.